Nanocarriers in Atopic Dermatitis Therapy: A Comprehensive Exploration - Rezigue, Meriem; Bashatwah, Rasha M.; Seetan, Khaled I.; Aljabali, Alaa A. A. (Pharmaceutical Nanotechnology, 2025)
In this comprehensive exploration of advanced nanocarriers for atopic dermatitis (AD) therapy, we explored a spectrum of innovative delivery systems, each with unique attributes poised to revolutionize topical drug administration. Lipid nanoparticles, including solid lipid nanoparticles (SLN) and nanostructured lipid carriers (NLC), have emerged as stalwarts offering controlled drug release and enhanced skin penetration. Vesicular systems such as liposomes, ethosomes, transfersomes, and niosomes are versatile in their ability to encapsulate hydrophilic and lipophilic agents and overcome barriers to drug permeation. Microemulsions and nanoemulsions exhibit good stability and effective drug permeation, whereas the addition of polymeric nanoparticles allows for efficient targeting with less toxicity. AuNPs and AgNPs allow for targeted delivery and immune modulation, whereas skin lipids restore this barrier. siRNA-silenced genes are involved in inflammation, whereas immunobiologics reset immune responses. These nanocarriers offer tremendous opportunities for the personalized treatment of AD, reduction in systemic exposure, and enhancement of therapeutic efficacy. Overcoming formulation hurdles and instability concerns, in addition to an in-depth understanding of the possibility of achieving game-changing improvements in the management of AD, has placed nanocarriers at the forefront of new and personalized therapeutic approaches that would redefine the care of patients affected by this devastating disease.
Keywords: Nanocarriers